The effectiveness of two manual slim bristles toothbrushes among fixed orthodontic appliance patients - Lee, Jin Han; Asma Alhusna Abang Abdullah,; Nurul Asyikin Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research aimed to evaluate the oral hygiene status in fixed orthodontic appliance patients when using two different slim bristles toothbrushes and to assess patients’ toothbrush perception.Twenty six fixed orthodontic appliance patients participated in the six weeks prospective, crossover clinical trial. All patients used two different slim bristles toothbrushes (Toothbrush A and Toothbrush B) for two weeks each with a washout period in between. Gingival health and plaque value were assessed based on Löe & Silness Gingival Index and Silness & Löe Plaque Index at baseline, week 2, week 4 (washout) and week 6. At the end of the trial, patients’ toothbrush perception was assessed through questionnaire. All data were analysed using SPSS version 22.The mean age of the patients was 21.5 ± 4.3 years, with female predominant (n = 17, 65.4%). More than half were Malay (n = 15, 57.7%) and had tertiary education (n = 14, 53.8%). Patients could achieve good oral hygiene when using Toothbrush A (65.4%) and Toothbrush B (69.2%). However, the occurrence of gingivitis was significantly higher when using Toothbrush A (OR = 1.889, 95% CI = 1.207-2.957, p value < 0.05). Toothbrush B was felt to clean better (n = 14, 53.8%) while Toothbrush A was perceived to be easier to use (n = 14, 53.8%). Both toothbrushes maintained patients’ oral hygiene status. However, when using Toothbrush B, oral health status was better as it significantly reduced gingivitis occurrence compared to Toothbrush A. As for the toothbrush perception, most patients preferred Toothbrush A to be taken home.